Leg dynamic strength predictors of a pre-planned change of direction task in NCAA division I soccer players - Chiang, C. Y.; Bailey, C. A.; Sole, C. J.; Suchomel, T. J.; Sato, K.; Stone, M. H. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The purpose of this investigation was to evaluate the relationships between two types of vertical jumps and change of direction (COD) test in collegiate soccer players (n=24). 5-5 COD test was utilized to measure soccer athletes` COD ability. 3m acceleration (3mAcc), Total time (TT) and Partial time (PT) were measured by two sets of timing gates. Countermovement jump (CMJ) and static jump (SJ) with 2 different loading conditionings (0kg and 20kg) were employed to evaluate athletes` leg dynamic strength. Strong statistically significant relationships were found between COD test variables (r =0.71 to 0.90), and between vertical jump variables with PT and TT (r = -0.41 to -0.81). These results suggest that leg dynamic strength is vital for NCAA Division I soccer players` COD performance and SJ 0kg jump height can be used to predict for COD performance.